Cytogenetic and molecular cytogenetic characterization of 6 new cases of idiopathic hypereosinophilic syndrome - R Bigoni; A Cuneo; MG Roberti; R Milani; A Bardi; F Cavazzini; C Minotto; G Castoldi (Haematologica, 2000)
BACKGROUND AND OBJECTIVE: Idiopathic hypereosinophilic syndrome (HES) is defined as a peripheral blood eosiniphilia greater than 1, 500 cells/microL for longer than 6 months, absence of other apparent etiologies for eosinophilia and signs and symptoms of organ involvement. HES may be a reactive condition or a chronic myeloproliferative disorder but scanty information is available concerning its cytogenetic profile. DESIGN AND METHODS: Six patients with HES were studied by cytogenetic analysis. To increase the sensitivity of cytogenetic analysis, interphase FISH studies were performed to detect some cryptic chromosomal lesions involving the regions known to be frequently involved in myeloproliferative disorders (i.e. BCR/ABL, 5q31, 7q31.1, 11q23, 13q14, 17p13). Clinical parameters were recorded in all patients. RESULTS: A 3q deletion was detected in one patient; two unrelated clones with +14 and +11 were present in another patient who had a cryptic 5q31 deletion as disclosed by FISH; both patients had a mild clinical course. The 5q31 deletion was shown to involve the eosinophilic lineage and not the lymphoid cells. No chromosome abnormalities were found by karyotyping or interphase FISH in the remaining 4 cases. In two of these cases the clinical course was aggressive, with progressive leukocytosis and marked splenomegaly in one patient, central nervous system and cardiac involvement as well as bone marrow failure in the other. INTERPRETATION AND CONCLUSIONS: The 3q deletion, +11 and +14, and a cryptic 5q31 deletion involving the cells of the eosinophilic lineage are three novel chromosome abnormalities occurring in HES. We did not find a correlation between evolving or aggressive disease and the presence of chromosome anomalies. Our data confirm that HES is a clinically and biologically heterogeneous condition and suggest that more cases need to be studied to identify clinically significant chromosome changes in this rare condition. Some patients may benefit from treatment with interferon.